Buffalo Management Practices of Rural Farmers in Anakapalli District of Andhra Pradesh (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted in Munagapaka mandal of Anakapalli district of East Andhra Pradesh,  India and data were collected from 150 respondents through specially structured questionnaire by  random sampling method. The study revealed that the majority of the buffalo farmers (75.3%) stall  fed concentrate and roughages and 90% depended on bore wells as a source of drinking water for  their animals. About 59.3% of farmers cultivated fodder on their own or lease lands. About 78.6%  respondents fed colostrum within 1 hr of birth of calves. 80.6% respondents provided mineral mixture  to their buffaloes occasionally. 58.7% of farmers always observed heat signs in buffaloes.  Conventional types of housing were practiced by 74% of the respondents with kuccha flooring and  drainage system was improper. The sanitary condition of most mangers was found clean. 62% of the  farmers relied on natural light sources. The adoption of scientific feeding, breeding, and housing  practices were poor among the majority of the farmers and needed to be improved.
Keywords: Buffaloes; feeding; breeding; housing